Molecular detection of Babesia bovis in cattle in Al-Qadisiyah province: Khawla H. Sabbar and Noaman N. A,aiz - A,aiz, Noaman N. (The Iraqi Journal of Veterinary Medicine, 2017)
This study aim to determine Babesia bovis infection in cattle based on genetic methods. A total of 96 blood samples were collected from alive and slaughtered cattle from different areas in addition to the abattoir of Al-Qadisiyah province from December 2013 to August 2014. Real time polymerase chain reaction (RT.PCR) technique was used to detect the presence of the protozoan with the effect of animal’s age and sex in the infection rate 47.91 % (46/96) of examined cattle were given positive result to B. bovis infection. The highest infections were shown among the adult cattle (≥1 year), while there was non-significant difference (P>0.05) in the infection rate according to the sex. So the most cattle in Al-Qadisiyah province appear to be bearing the infection predominantly as a carrier hosts.